Screening of cyanobacterial strains for toxicity assay Of silver and silver nanoparticles - SADAF MAHFOOZ; ZAIRISH IMRAN; ADEEBA SHAMIM; ALVINA FAROOQUI (International Journal of Pharma and Bio Sciences, 2016)
The growing incorporation of nanomaterials and excessive heavy metal discharge into the environment calls for the better understanding of their toxicological effects on the ecosystem. For analyzing their toxic effects we have chosen cyanobacteria as our model system. Cyanobacteria is known to accumulate heavy metals and act as a sink for many aquatic contaminants. The present study aims towards screening of four cyanobacterial strains namely Synechococcus sp., Scytonema sp., Nostoc muscorum and Plectonema boryanum, against silver stress. Our results indicated that out of four strains, two strains namely Nostoc muscorum and Plectonema boryanum were found to be less sensitive while Scytonema sp. exhibited highest sensitivity towards Ag stress. Our results state that the growth inhibition of cyanobacterial strains is in the order of Scytonema sp> Synechococcus sp >Nostoc muscorum> Plectonema boryanum which was estimated in terms of photosynthetic pigment (Chl a). Effect of Ag stress on carotenoids (Car) and total protein was also studied. Based on the above results, the less sensitive strains namely Nostoc muscorum and Plectonema boryanum were further studied against silver nanoparticles stress. All experiments were repeated three times to ascertain the reproducibility of the results. Values are represented as mean ± SE. Thus, the understanding of the responses incurred in cyanobacteria during heavy metal and metal nanoparticle stress can be very well used to evaluate their toxic responses in the environment.